Sustaining EU financing for security and development: the difficult case of the African peace facility - Mark Furness (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Africa's peace and security architecture needs European support to manage sustainable, comprehensive peacebuilding on the continent, thereby establishing the necessary conditions for socio-economic development. This is a long-term process which requires political commitment and reliable financing. Since 2004, the African Peace Facility (APF) has become invaluable for supporting African Union (AU)-led peace support operations (PSOs). Its added value and potential for supporting African peacebuilding have been confirmed by independent evaluations in 2005 and 2011. The AU and EU Commissions are enthusiastic about continuing the APF cooperation and improving the instrument's flexibility and efficiency. The APF is financed from the European Development Fund (EDF) for legal reasons: the European Union Treaties do not allow Community funds to finance military operations. The EDF is not part of the EU budget but is funded directly by member states and has different rules. This was meant to be a temporary arrangement and is unsustainable, especially if member states decide to include the 11th EDF in the 2014–2020 EU budget. In the medium term the whole spectrum of EU relations with African, Caribbean and Pacific (ACP) partners and the corresponding financial instruments will be under review when the Cotonou Agreement expires in 2020. Aside from these technical issues, the main problem for the APF is its capacity. In its present form it is unlikely to be able to meet demand in the next few years as pressure for expanding the AU mission in Somalia grows, and new missions become necessary. A sustainable source of funding for PSOs in Africa will have to be found. The upcoming EU budget negotiations provide an opportunity to reconsider this complex issue. The choice for the EU boils down to three options: 1. Continue to fund the APF from the EDF, especially if the EDF remains outside the EU budget until 2020. 2. Finance the APF from the EU budget, possibly combining it with the Instrument for Stability (IfS) or the Common Foreign and Security Policy (CFSP) instrument. 3. Create an entirely new instrument outside the EU budget specifically for supporting PSOs conducted by non-EU multilateral organisations. The EU and its member states have a strategic interest in long-term peace and stability in Africa. Europeans also have a moral duty to contribute to conflict prevention and peaceful relations within and between societies in Africa and elsewhere. Paying the expenses of third country soldiers is a necessary component of the shared strategy for reaching these goals, and providing an adequate financial instrument should not be beyond Europe's capabilities. The third option would provide the best source of predictable funding for supporting PSOs in Africa and potentially Asia and the Middle East also.
Keywords: 330